When Justice Overrides Procedure: Unpacking the Reluctance to Apply SEMA No. 3 of 2023 in Verstek Divorce Cases - Mutsaniyah, Maghfirotul; Alyaa, Nurul Syazana (Islamic Family Law Study Program, Sharia Faculty, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study investigates the non-application of Supreme Court Circular (SEMA) No. 3 of 2023 in verstek (default) divorce decisions at the Jember Religious Court, highlighting the underlying judicial reasoning and its implications for legal uniformity. While SEMA No. 3 of 2023 was introduced to guide judicial practice—particularly in ensuring procedural fairness in divorce cases—this research reveals that it is not consistently used as a reference in verstek rulings. Through qualitative analysis, including interviews with judges and examination of court decisions, the study finds that the judges prioritize the specific circumstances of each case, often relying more heavily on the legal facts revealed during the trial and on considerations of maṣlaḥah (public interest or welfare). Judges argue that rigid adherence to procedural guidelines may, in certain contexts, lead to greater injustice, particularly when it delays the legal resolution for aggrieved parties. The study further identifies a pattern of legal disparity resulting from differing interpretations and applications of SEMA provisions. This inconsistency not only contributes to uncertainty in legal outcomes but also poses a risk to public trust in the judiciary. The paper argues that to enhance legal certainty and consistency, the principles embedded in SEMA No. 3 of 2023 should be codified into binding legislation. Moreover, it recommends a re-evaluation of the normative and authoritative status of Supreme Court Circulars within Indonesia’s judicial framework. This research contributes to the broader discourse on judicial discretion, procedural justice, and the balance between legal formalism and substantive fairness in Islamic family law adjudication.